Glycyrrhiza glabra - Kočevar Glavač, Nina (Farmacevtski vestnik, 2008)
Glycyrrhiza glabra has been used for the treatment of upper respiratory tract inflammation and ulcer disease. In the article, a review of therapeutic uses, pharmacological activities, and toxicological effects are presented.
Keywords: farmakologija; sladki koren; toksikologija